This is an arithmetic sequence with initial term a = 3 and common difference d = 2. Using the nth term formula for arithmetic sequences
an = a + (n - 1)d
we get an = 3 + (n - 1)(2) = 2n - 2 + 3 = 2n + 1.
If you mean: 3, 4, 5, 6 and 7 then nth term = n+2
The nth term of the sequence is 2n + 1.
Un = 4n - 9
2n+5
12 - 5(n-1)
It is: nth term = 5-4n and so the next term will be -19
If you mean: 3, 4, 5, 6 and 7 then nth term = n+2
If you mean -1 3 7 11 15 then the nth term is 4n-5 and so the next term will be 19
The nth term of the sequence is 2n + 1.
Un = 4n - 9
2n+3. If 5 is the first term, then it is 2n + 3 (2×1 = 2 + 3 = 5 and 2×2 + 3 = 7)
7 - 4n where n denotes the nth term and n starting with 0
2n+5
12 - 5(n-1)
The nth term in this sequence is 4n + 3.
2n + 1
If you mean: 15 11 7 3 then the nth term is 19-4n